Kohesi Gramatikal dan Leksikal dalam Keterangan Instagram Folkative - Norlistian, Ellen Austin; Sabardila, Atiqa (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study aims to determine the aspects of grammatical cohesion and lexical cohesion contained in the quotation of folkative Instagram posts. This research uses descriptive qualitative method with the subject of this research is the description of Instagram posts from the Folkative account. The object of this research is the words and sentences listed in the Instagram post caption of the folkative account. The data analysis technique used is descriptive technique, with data collection of read and write. The results of this study found grammatical cohesion in the form of references with 29.41% and conjunctions with 52.94%. While lexical cohesion is found in the form of repetition with 11.76% and hyponymy with 5.88%. The dominant aspect in the quotation of folkative Instagram posts is the aspect of conjunction grammatical cohesion with a percentage of 52.94%.